Evaluation of the efficacy of hydrated sodium aluminosilicate in the prevention of aflatoxin-induced hepatic cancer in rainbow trout - Sarah Arana; Maria L. Z. Dagli; Myrna Sabino; Yara A. Tabata; Marcos G. Rigolino; Francisco J. Hernandez-Blazquez (Pesquisa Veterinária Brasileira, 2011)
The use of aluminum silicates for decontaminating animal feed containing aflatoxins has yielded encouraging results in chicken and turkey poults. In contrast, very few studies have tested these substances in aquaculture. In this work, we investigated the efficacy of a trout diet containing 0.5% hydrated sodium aluminosilicate (HSAS) in protecting against contamination with aflatoxin B1. Trout were reared on these diets for one year and the experimental groups were examined monthly for hepatic presumptive preneoplastic and neoplastic lesions. Regardless of the presence of HSAS, all of the fish that received aflatoxin in their diet have shown hepatic lesions indicative of a carcinogenic process, presenting also the development of cancer in some fish. The concentration of HSAS used in this study was ineffective in preventing the onset of hepatic lesions induced by aflatoxin B1 in rainbow trout.